PENGARUH PERTUMBUHAN PENJUALAN, KONSERVATISME AKUNTANSI, DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE - Jaka Saputra; Purwatiningsih Purwatiningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of Sales Growth, Accounting Conservatism, and Fiscal Loss Compensation on Tax Avoidance in manufacturing companies in the pharmaceutical sub-sector consumer goods industry listed on the IDX for the 2016 - 2020 period. Sales Growth Variable is measured by NSGR, Accounting Conservatism is measured by KNSV, Fiscal Loss Compensation is measured by Dummy Variable, and Tax Avoidance is measured by CETR. This research is a quantitative study and uses secondary data in the form of annual financial reports from the IDX. The sampling technique used purposive sampling method, obtained 10 pharmaceutical companies as research samples. The data analysis tool uses the Eviews version 12 software program. The results show that Sales Growth and Accounting Conservatism have a significant positive effect on Tax Avoidance, while Fiscal Loss Compensation has no effect significant to Tax Avoidance.